Sedimentary CaCO3 Accumulation in the Deep West Pacific Ocean - Zhang, Handan; Che, Hong; Xia, Jinqi; Cheng, Qi; Qi, Di; Cao, Junqian; Luo, Yiming (Frontiers in Earth Science, 2022)
Distribution of calcium carbonate (CaCO3) in marine sediment has been studied over the last century, and influence by multiple factors with regard to dissolution and dilution of sedimentary CaCO3 has long been established. Yet, there is still lack of quantification on the influence of those factors, so that it remains elusive to determine which specific process is driving the down-core variation of CaCO3 content (wtCaCO3%) records. Here, based on a newly compiled CaCO3 data set and a carbonate model, depth-profiles of sedimentary wtCaCO3% from the West Pacific Ocean can be well illustrated and influence from different factors on their distribution features can be quantified. The deep ocean circulation is found to largely shape the inter-basin disparity in sedimentary wtCaCO3% distribution between the equatorial regions (e.g., the Western Equatorial Pacific Ocean and the Central Pacific Ocean) and the north-west regions (the Philippine Sea and the Northwest Pacific Ocean) in our study region. Moreover, the slow carbonate dissolution rate in the deep Central Pacific Ocean guarantees better accumulation of CaCO3 at depth compared to that in other regions. However, enhanced dilution by non-carbonate materials of sedimentary CaCO3 on topographic complex can potentially obstruct the dissolution profiles constituted by sedimentary wtCaCO3% in the pelagic ocean. The above assertion suggests that changes of wtCaCO3% accumulation in marine sediment in the west Pacific Ocean can be used to dictate past changes of the deep ocean circulation (2,500 to 3,000 m) in this area, but constraint on the non-carbonate flux especially on topographic complex should be necessary.